Clinical approach to the patient with acute gastrointestinal bleeding - Gaiani, Federica; de’Angelis, Nicola; Kayali, Stefano; Manfredi, Marco; di Mario, Francesco; Leandro, Gioacchino; Ghiselli, Alessia; Fornaroli, Fabiola; de’Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Gastrointestinal bleeding (GIB) is a very common condition at all ages, with high rates of morbidity and mortality, especially in case of acute presentation. The optimal management of acute GIB requires a timely overview of vital signs and clinical presentation to stabilize the patient if necessary and set up the most adequate diagnostic and therapeutic approach, based on the suspected etiology. Endoscopy plays a major role both in diagnosis and treatment of acute GIB, as allows the application of several hemostasis techniques during the diagnostic session, which should preferably be performed within 24 hours from the acute event. The hemostasis technique should be chosen based on type, etiology of the bleeding and the operator preference and expertise. Nevertheless, several challenging cases need the cooperation of radiology especially in the diagnostic phase, and even in the therapeutic phase for those bleedings in which medical and endoscopic techniques have failed. Imaging diagnostic techniques include mainly CT angiography, scintigraphy with labeled erythrocytes and arteriography. This last technique plays also a therapeutic role in case arterial embolization is needed. Only those patients in which the previous techniques have failed, both in diagnosis and treatment, are candidates for emergency surgery.